Hermetic sealing of MEMS sensors for high temperature electronics applications - Muhammad Afiq Sani. (2012)
In this study, 100 μm sealing width of both Al-Ge eutectic bonds and Pt-In Transient Liquid Phase bonds were fabricated and evaluated. The experiments were conducted to determine the feasibility of the bonding for usage in high temperature applications.